Diagnostic effectiveness of anti-citrullinated peptides antibodies of second and third generations for rheumatoid arthritis - Goitybell Martínez Téllez; Bárbara Torres Rives; Jorge Alexis Gómez; Dinorah Prada Hernández; Vicky Sánchez Rodríguez (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Rheumatoid arthritis is an autoimmune disease characterized by the presence of antibodies against citrullinated peptides, which are one of the indicators for the diagnosis of a disease.  The usefulness of different methods for the determination of these antibodies in the diagnosis of Cuban patients with rheumatoid arthritis is necessary to be established. Objective: To establish the diagnostic effectiveness of the second (anti-CCP2) and third (anti-CCP3) generation assays for the determination these antibodies against citrullinated peptides in Cuban patients with rheumatoid arthritis. Material and method: 101 patients with rheumatoid arthritis, 58 patients with other rheumatic and inflammatory diseases, and 43 healthy persons participated in the study. The diagnostic efficiency of rheumatoid factor (RF), anti-CCP2 and anti-CCP3 antibodies were determined using ELISA test, by calculating sensitivity, specificity, and positive and negative predictive values. Results: The anti-CCP2 assay showed a better balance of sensitivity (48.5 %) and specificity (98.0 %).  The lower sensibility was observed for RF (40.3%) when the specificity was set at 98 %. Specificity increased to 100% when anti-CCP2 and RF assays were used. All autoantibodies showed association with C-reactive protein and correlation with erythrocyte sedimentation rate. Only anti-CCP2 antibodies showed no correlation with the DAS28 clinical indicator. Conclusions: Anti-CCP2 antibodies are the ones of greater effectiveness in the diagnosis of Cuban patients with rheumatoid arthritis. RF identification allows to identify seronegative anti-CCP2 patients; therefore, the combination of both immunoassays leads to an improvement in the diagnostic effectiveness.   Keywords: Rheumatoid arthritis, cyclic citrullinated peptide, antibodies, anti-CCP2, anti-CCP3, diagnosis.